Late complications of hemispherectomy: report of a case relieved by surgery. Issue 3 (June 1970) - Mathew, Ninan T.; Abraham, Jacob; Chandy, Jacob
Abstract : A case of Sturge-Weber disease treated with left hemispherectomy presented, 11 years later, with complications related to delayed intracranial haemorrhage. A loculation syndrome of the right lateral ventricle was detected and it was corrected by a ventriculoatrial shunt operation. The side of the hemispherectomy was evacuated of all the chronic products of haemorrhage, including the subdural membrane. The patient was relieved of her symptoms. It is considered that complications related to delayed haemorrhage after hemispherectomy are remediable.